Financial Development, Energy Supply and Environmental Quality in West Africa - Kolawole, Kayode (International Journal of Energy Economics and Policy, 2026)
This research investigates the influence of financial development and energy supply on environmental quality in West Africa. The study's data spans from 2009 to 2023 and was obtained from the World Development Indicator database. We employed the panel autoregressive distributed lag (P-ARDL) estimator for the analysis. Empirical evidence indicated that private sector lending substantially influences environmental quality in West Africa. Access to electricity dramatically influences environmental quality in West Africa. This illustrates that investment in the private sector and sufficient electricity generation enhance environmental quality within the West African economy. The study concludes that financial development and energy supply significantly influence environmental quality. The report advises that West African financial institutions should establish green financing methods to direct loans towards environmentally non-polluting projects.